2005
DOI: 10.1681/asn.2004121075
|View full text |Cite
|
Sign up to set email alerts
|

IL-12p40 and IL-18 in Crescentic Glomerulonephritis

Abstract: Experimental crescentic glomerulonephritis (GN) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
88
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 41 publications
6
88
1
Order By: Relevance
“…3 This pathophysiological concept is mainly based on findings from experimental rodent models of glomerulonephritis. Renal T cell and monocyte recruitment and subsequent tissue damage are attenuated in mice with genetic deletion of Th1 cytokines such as IL-12 p40 4 and IFN␥ 5 and by blocking of Th1 cytokines with inhibitory antibodies including anti-IL-12 p40(p35) 6 and anti-IFN␥. 7 Furthermore, exogenous administration of IL-12 augments Th1 responses and crescentic glomerulonephritis.…”
Section: Il-17mentioning
confidence: 99%
“…3 This pathophysiological concept is mainly based on findings from experimental rodent models of glomerulonephritis. Renal T cell and monocyte recruitment and subsequent tissue damage are attenuated in mice with genetic deletion of Th1 cytokines such as IL-12 p40 4 and IFN␥ 5 and by blocking of Th1 cytokines with inhibitory antibodies including anti-IL-12 p40(p35) 6 and anti-IFN␥. 7 Furthermore, exogenous administration of IL-12 augments Th1 responses and crescentic glomerulonephritis.…”
Section: Il-17mentioning
confidence: 99%
“…IL-12, a heterodimer composed of IL-12p40 and IL-12p35 subunits, is the key cytokine in Th1 differentiation. Studies using neutralizing antibodies and IL-12p40 Ϫ/Ϫ mice, including studies in experimental glomerulonephritis, seemed to define an important role for IL-12 in both autoimmune 17 and nonautoimmune 18,19 glomerulonephritis; however, the subsequent discovery of IL-23, a newer IL-12 family member that is also a heterodimer (composed of IL-12p40 and IL23p19 subunits), prompted a reevaluation of studies that used IL-12p40 Ϫ/Ϫ mice and anti-IL-12p40 antibodies. Other lines of evidence have defined IL-23 as important for the maintenance of the Th17 subset and implicated Th17 in the pathogenesis of organ-specific autoimmune disease.…”
Section: J Am Soc Nephrolmentioning
confidence: 99%
“…IFN-␥ and IL-4 in splenocyte supernatants were measured by ELISA, as described previously. 19,44 IL-17A, TGF-␤1, IL-12, and IL-23 were measured by ELISA: IL-17A and TGF-␤1 (R&D Systems, Minneapolis, MN) and IL-12 and IL-23 (eBioscience) as per the manufacturers' protocols. IL-6, IL-10, monocyte chemoattractant protein 1, IFN-␥, TNF, and IL-12p70 were also measured by flow cytometry using a cytometric bead array mouse inflammation kit (BD Biosciences), as per the manufacturer's protocol.…”
Section: Dermal Dth Responses and Cytokine Productionmentioning
confidence: 99%
“…[7][8][9] It is increasingly evident that proinflammatory cytokines and growth hormones released by proliferating cells in the glomerulus are involved in the pathogenesis of crescent formation. [10][11][12][13] These factors stimulate the p38 mitogen-activated protein kinase (MAPK) pathway, resulting in the production of inflammatory mediators. [14][15][16] The involvement of the MAPK pathway in the pathogenesis of CGN was first reported by Bokemeyer et al, 17 who demonstrated a rapid and sustained activation of extracellular signal-regulated kinase in the glomeruli isolated from rat model of anti-GBM nephritis.…”
mentioning
confidence: 99%